Smart Governance dalam Pengelolaan Transportasi Perkotaan di Kota Makassar: Digitalisasi Mobilitas Berkelanjutan dan Perencanaan Kota - Syafaruddin Syafaruddin; Ambo Masse (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The purpose of this study is to focus on the role of innovative governance in supporting the digitalization of sustainable mobility to improve the efficiency and accessibility of urban transportation. This study aims to investigate the potential of the bright governance concept to accelerate digital transformation in Makassar City's transportation system. The research method used is a qualitative approach with data collection techniques through in-depth interviews, field observations, policy document analysis, and Focus Group Discussions (FGD). Key informants include local governments, transportation operators, academics, and community users of transportation services. The data obtained were analyzed using NVivo 12 Plus to identify patterns and relationships in digital transportation policies. The findings of this study indicate that transportation digitalization in Makassar City through Teman Bus Trans Mamminasata, QRIS payments, and intelligent transportation systems has successfully improved the efficiency, transparency, and quality of public services, as seen from the increase in the number of passengers despite still facing challenges such as declining interest in paying fares, public preference for private vehicles, limited information, and competition from other modes. The sustainability of this innovation depends on the implementation of an innovative governance model with cross-sector collaboration, data transparency, public participation, and analytics-based decision-making to realize modern, inclusive, and sustainable urban mobility in Makassar.